Effect of copolymerization on the thermal characteristics and behavior of crystallization of biobased semi‐aromatic PA10T/10I. Issue 22 (4th April 2023) - Zhu, Rongli; Pu, Zejun; Hou, Hongbo; Li, Xianyong; Wang, Xu; Yu, Dayang; Zheng, Pan; Wu, Fang; Zhong, Jiachun
Abstract: This work synthesized the pure poly (decamethylene terephthalamide) acid (PA10T) and a series of PA10T/10I through an efficient one‐pot melt polymerization method. The structures, thermal behavior, crystallization performance, and mechanical properties of PA10T and PA10T/10I were investigated by FT‐IR, DSC, TGA, POM, XRD, and mechanics performance testing, respectively. The thermal analysis demonstrates that the melting temperature of PA10T/10I gradually decreased with the increase of isophthalic acid (IPA) copolymerization proportions. Specifically, it was observed that, the T m1 of pure PA10T was 299.5°C, while the T m1 of PA10T/10I‐4 with a linear downward trend was 284.7°C. And the introduction of IPA copolymerization has an obvious beneficial effect on the thermal stability of PA10T/10I ( T d, 5 varied from 429.5 to 434.5°C) with a wider temperature range of processing, which could potentially be applied in high‐temperature scenes. POM and XRD were used to characterize the crystallization behavior of all samples further. It was discovered that although adding IPA did not alter the crystal structure of PA10T, it dramatically reduced the size of crystalline grains and increased the number of crystal nuclei. In addition, the copolyamides possess excellent mechanical properties, and the tensile strength of PA10T/10I varied between 42.91 and 46.89 MPa, the bending strength varied between 76.69 and 85.83 MPa, and the izod impact strength varied between 25.41 and 29.82 kJ m −2 . Moreover, the influence of the IPA comonomer of copolyamides PA10T/10I on melting points, thermal stability, crystallization behavior, and mechanical characteristics was investigated. This work provides a reference for preparing biobased semi‐aromatic copolyamides PA10T/10I with outstanding processing performance, excellent thermal characteristics, and adjustable mechanical properties. Abstract : This work synthesized a series of biobased semi‐aromatic copolyamides PA10T/10I with PTA, IPA, DMD, and benzoic acid through an efficient one‐pot melt polymerization method. The results indicate that PA10T/10I copolyamides possess outstanding processing performance, thermal characteristics, and mechanical properties, and have wider applications to meet multifarious requirements.